HIV/AIDS-related knowledge and attitudes toward people living with HIV among college students in Xuzhou, Jiangsu Province, China: a cross-sectional survey - Li, Hualing; Wu, Qi; Gao, Enze; Zhang, Ying; Yin, Dehui (Frontiers in Public Health, 2024)
Background In the contemporary landscape, college students have emerged as a demographic increasingly vulnerable to AIDS. Recognizing that heightened awareness and progressive attitudes toward HIV are pivotal in its prevention, this study was conceived with the intent to meticulously evaluate the level of HIV understanding amongst college students, gauge their sentiments toward people living with HIV (PLHIV), and scrutinize factors influencing these perceptions. Method This study used an anonymous online questionnaire to collect data through a cross-sectional survey. The sample size for the survey was 4,193 students from four colleges and universities in Xuzhou City, Jiangsu Province, China, covering a variety of demographic characteristics. The survey focused on students’ level of knowledge related to HIV and their attitudes toward PLHIV. The study used descriptive statistics to describe the demographic characteristics of the sample, chi-square tests to examine differences within categorical variables, and logistic regression to investigate the associations between knowledge levels and attitudes. Results A total of 4,193 university students were surveyed, among whom the majority (96.85%) demonstrated a high level of knowledge related to AIDS. Moreover, 55.52% of the participants reported positive attitudes toward individuals with AIDS. The multiple regression analysis revealed that female students (OR = 0.49, p < 0.001), those enrolled in medical programs (OR = 1.56, p = 0.014), students of Han Chinese ethnicity (OR = 2.46, p = 0.009), and individuals with fewer romantic involvements (OR = 1.57, p < 0.001) possess greater HIV/AIDS awareness. Moreover, lower grade levels (OR = 1.12, p < 0.001), reduced monthly living costs (OR = 1.14, p = 0.014), lack of sexual experience (OR = 0.75, p = 0.015), and a higher degree of HIV/AIDS knowledge (OR = 1.617, p = 0.007) were positively correlated with supportive attitudes toward PLHIV. Conclusion Overall, the awareness rate of college students in Xuzhou City about HIV/AIDS infection awareness is high. However, only about half of the university students have positive attitudes toward PLHIV. In order to ensure that a thorough understanding of HIV/AIDS is matched by positive attitudes, it is important to implement targeted educational measures aimed at bridging the gap between knowledge and attitudes toward HIV/AIDS in order to develop a more informed and empathetic student body.